HIGHLIGHTS OF SEVERAL WORKS ON METAPHYSICS AND TASAWWUF - Wirman, Metsra (JURNAL AL-AQIDAH, 2020)
This article is a summary of the important points in the subject of philosophy of science, especially, Metaphysics idea or in Islamic sense. It calls as “Tasawwuf” (Islamic metaphysics). From several works, for instance, Immanuel Kant’s Prolegomena to Any Future Metaphysics, S.M.N al-Attas’s Islam and the Philosophy of Science, and Nūr al-Dīn al-Rānirī’s Latā’if al-Asrār li Ahli Allah al-Aṭyār. From these three books, here is the highlight in order to understand their views on Metaphysics and Tasawwuf. The survey aims to analyze and compare their views, particularly on pertaining on Metaphysics. The study was found that Metaphysics, deals in general with questions about the nature of reality. The Sufis took the same position as the philosophers and the theologians in affirming the reality of thing that constitute the world, and hence also the reality of the world, as established, in contradiction to the Sophists. But the Sufis attested further, in significant contrast to the philosophers and the theologians, that in addition to existence in the above sense, that is, as a pure concept, and based upon clear mystical revelation and true intuition founded upon the authority of the Holy Qur’an and the tradition as well as upon reason and experience.  Keywords: Epistemology, Metaphysics, Philosophy of Science, Reality, Sufism (Tasawwuf), Truth.